2012
DOI: 10.1371/journal.pone.0032143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum HBsAg Quantitation by Four Immunoassays, and Relationships of HBsAg Level with HBV Replication and HBV Genotypes

Abstract: BackgroundThe decline in hepatitis B virus surface antigen (HBsAg) may be an early predictor of the viral efficacy of Hepatitis B virus (HBV) therapy. The HBsAg levels obtained by different immunoassays now need comparing and the relationships between levels of HBsAg and HBV DNA alongside HBsAg and genotype must be evaluated.Methodology/Principal FindingsHBsAg levels were compared among 80 patients using the Abbott Architect assay, a commercial immunoassay approved for HBsAg detection and quantitation, and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
(48 reference statements)
2
23
0
Order By: Relevance
“…A recent study evaluated the correlation between HBV DNA and HBsAg levels according to HBV genotype. These investigators found that serum HBsAg level tended to correlate with HBV DNA level for genotype A, but did not reach significant for genotype D (Tuaillon et al 2012). We recently followed 187 patients with chronic HBV infection for a median of 8 years.…”
Section: Clinical Significance Of Quantitative Hbsag and Its Correlatmentioning
confidence: 95%
“…A recent study evaluated the correlation between HBV DNA and HBsAg levels according to HBV genotype. These investigators found that serum HBsAg level tended to correlate with HBV DNA level for genotype A, but did not reach significant for genotype D (Tuaillon et al 2012). We recently followed 187 patients with chronic HBV infection for a median of 8 years.…”
Section: Clinical Significance Of Quantitative Hbsag and Its Correlatmentioning
confidence: 95%
“…This analytical sensibility is generally insufficient to meet the minimum requirements of European regulatory authorities and WHO (Lower limit of detection (LOD) < 4 IU/mL) (Chevaliez et al, 2014; World Health Organization [WHO], 2019). HBsAg laboratory tests have a sensitivity <0.1 IU/mL (Tuaillon et al, 2012), suggesting that even with a dilution factor of 10 or 20 times related to the elution step, the DBS testing may have a better sensitivity than HBsAg RDT. Systematic reviews have reported 98% sensitivity and 100% specificity for HBsAg screening on DBS compared to 88.9% sensitivity and 98.4% specificity using HBsAg RDT Lange et al, 2017a).…”
Section: Dbs For Screening and Serologic Confirmation Of Hiv And Viramentioning
confidence: 99%
“…A new assay was developed for measuring HBV core-related antigen (HBcrAg), which consists of a core, e antigen (HBeAg), and the precore HBV proteins (22-kD precore fragment, amino acids 28-150); HBcrAg levels correlated well with HBV DNA levels [15]. A recent study showed that the serum HBcrAg concentration was related to the level of intrahepatic cccDNA [16]. Until recently, and for more than a decade, only 1 commercial qHBsAg assay was available [15].…”
Section: Hbv (Hepatitis B Virus)mentioning
confidence: 99%